Dia Bukan Perempuan Gila: Mengunjungi Kembali Ayub 2:9-10 dengan Perspektif Feminis dan Teori Maskulinitas - Nixon, Grant (Asosiasi Teolog Indonesia, 2025)
The figure of Job is shared among Abrahamic traditions. Christian readings of Job’s wife are dominated by masculinist perspectives that erase gender dynamics within patriarchal society. Unlike the Islamic tradition, which portrays Job’s wife as a faithful woman who stands by Job in his afflictions, the Jewish-Christian tradition associates Job’s wife with being a tool of Satan to test Job’s faith. This article aims to revisit the Christian interpretation of the dialogue between Job’s wife and Job, with special attention to gendered imbalances of power both in the text and its reception. Through socio-historical analysis, I explore gender dynamics during the text’s formation to sketch the complexity of the roles and social locations of women in antiquity. Employing Elisabeth Schüssler Fiorenza’s hermeneutics of suspicion to engage a progressive interpretation lens, I portray Job’s wife as an autonomous and resistant woman within a space of systemic injustice. Consequently, I critically analyze Job’s rebuke in saying to his wife, “You speak as one of the foolish women would speak” (Job 2:10, ESV), arguing that this remark presents a reflective narrative that serves as self-criticism for men who enjoy the privileges of a patriarchal society. Furthermore, I contend that this rebuke mirrors a crisis of masculinity among men in religious spaces who are prone to using power and mystical premises to silence women’s voices. Absent any intent to co-opt women’s voices, I conduct this reinterpretation in solidarity with women and, as a man, intend it as a contribution to the struggle for gender equity, particularly in the interpretation of religious texts.